2021
DOI: 10.3390/su132212932
|View full text |Cite
|
Sign up to set email alerts
|

Using Fuzzy AHP-PROMETHEE for Market Risk Assessment of New-Build River Cruises on the Yangtze River

Abstract: Cruise tourism on the Yangtze River Basin has developed rapidly in recent years. However, it is still facing such challenges as homogenization of itinerary and shore attraction arrangement, as well as aging cruise ships and simplification of service facilities, while it is also difficult to satisfy hierarchical and personalized tourist needs. To change such circumstances, new-build river cruise ships are inevitable. Complexity of market supply and demand environment, together with variability of tourist prefer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In response to the results of the questionnaire analysis, the semi-structured interview method was used to collect the opinions of 10 respondents with relevant industry and academic backgrounds, as shown in Table 4. Finally, after all the information was integrated, the information was cross-compared with the processes of classification, induction, and sorting, and the multi-check analysis method was used to discuss [51][52][53].…”
Section: Data Processing and Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…In response to the results of the questionnaire analysis, the semi-structured interview method was used to collect the opinions of 10 respondents with relevant industry and academic backgrounds, as shown in Table 4. Finally, after all the information was integrated, the information was cross-compared with the processes of classification, induction, and sorting, and the multi-check analysis method was used to discuss [51][52][53].…”
Section: Data Processing and Analysismentioning
confidence: 99%
“…However, most of the topics discussed are tourism development and impacts [19,[22][23][24][25], freshwater intake sources and strategies [41], water quality and monitoring [42], carbon emissions [43], hydrology [44], water pollution [45], and marine and freshwater ecosystems [46]. In addition, the current research topics focusing on the Yangtze River only focus on air pollution [47], water pollution [48], energy utilization rate [49], urban land development and utilization rate [50], cruise tourism development [51], and residents' environmental literacy and decision-making participation [52]. Most of them are simply discussed from a single perspective, such as that of residents and tourists [51][52][53], but there is no hybrid research method, and most are based on the perspective of consumer willingness to buy property, revisit, or the two perspectives combined to discuss together.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lots of researchers have suggested that diversification is one of the key influencers leading to sustainable tourism development [3,4]. Homogenization not only diminishes the competitive edge of individual tourist destinations [5] but also poses a potential threat to the integrity of ecological landscapes [6]. Therefore, revealing the homogenization phenomenon in tourist destinations is a significant topic.…”
Section: Introductionmentioning
confidence: 99%